Faktor-Faktor Yang Berhubungan Dengan Pemberian Asi Ekslusif Pada Ibu Muda Di Wilayah Kerja Puskesmas Banyudono 1 Dan Banyudono 2, Boyolali - Cristiana, Elisa Nova; , Anisa Catur Wijayanti, SKM., M.Epid; , Kusuma Estu Werdani, SKM., M.Kes (2016)
Breast milk was the baby food was high in nutrients that were needed baby. According to the Demographic and Health Survey in 2012, Indonesia only had the scope of exclusive breastfeeding by 54,3%, in Central Java at 58.4%, and Boyolali in 2014 by 62%, the coverage is still below the target of 80% of healthy Indonesia. The magnitude of risk for the young mother did not breastfeed their babies may decrease the rate of exclusive breastfeeding in the coverage area Boyolali. Mothers Knowledge, employment status, and family support to be a factor that can affect the success of exclusive breastfeeding. The purpose of this research was to analyze the factors associated with exclusive breastfeeding for young mothers in the working area health centers Banyudono 1 and Banyudono 2, Boyolali. This type of research is observational with approached of cross sectional. Population in this research were all breastfeeding mothers aged ≤20 years, having babies older than 6 moths and stand in Puskesmas Banyudono 1 and Banyudono 2, Boyolali were 48 people with exhaustive technique. The statistic test technique used chi square. The result of this research showed that there was relationship among mother's knowledge (p=0,02), family support (p=0,013), and are not related among the employment status (p=0,63) with exclusive breastfeeding for young mothers in Puskesmas Banyudono 1 and Banyuodono 2.